Multimodal Analysis of the Political Posters before Election Campaign (2018) in Pakistan - FaizaAbid; RidaSarfraz; Ashfaq, Naheed; Niazi, Aisha (International Journal of Psychosocial Rehabilitation, 2020)
This paper will analyze the political posters used for election campaignsof different but prominent Pakistani political parties like Pakistan Peoples Party (PPP), Pakistan Tehreek e Insaaf (PTI) and Pakistan Muslim League Noon (PML-N).The study will supremely focus on the representation of their leader through posters and later on it will pinpoint the similarities and possible differences between each of the poster especially emphasizing on what they denote. To instigate the target audience to vote for the particular party itis significant to study the main linguistic and visual strategies. That is used to highlight the power and presence of a politician. While keeping in mind the cult of persuasion we must concentrate that how these parties grip the audience/ voters to an emotional extent that they actually get seriously attached with the concerned party.For the analysis, this research will focus on nine significant posters that have been selected randomly. These posters belong to three prominent Political parties that are present in the country. They will use these postersin the election campaigns’2018 and will roll these throughout the country for their target audience. Therefore, the researcher has used critical discourse analysis tools to identify the discursive strategies used. These strategies will help to persuade the Pakistani population to vote for their preferred politician. Van Leeuwen’s (2008), social actor theory will assist in order to understand of how participants are represented. As far as images are concernedKress and van Leeuwen’s(2006) visual grammar will be use.These politicians have been symbolically treated as to inspire the masses and presented as warriors and saviors that can lift up the misery from people. These posters have chronic impact on the psychology of the people that instigate them to vote or to support their respective party Furthermore, this study will also probe various tactics that have been implied by the political partiesin their posters to create a powerful discourse that hit audience emotionally and provoke them for specific action.